Precursor ratio optimizations for the synthesis of colloidal CZTS nanoparticles for photocatalytic degradation of malachite green. (November 2018) - jain, Shefali; Singh, Akanksha; Gupta, Govind; Vijayan, N.; Sharma, Shailesh Narain
Abstract: Cu2 ZnSnS4 (CZTS) is a foremost applicant material for photovoltaics application constituting environmentally friendly elements in Zn- rich Cu-poor configuration (Zn/Sn > 1, Cu/(Zn + Sn) < 1) with a direct band gap of 1.5 eV. However, with the changes in precursor ratio, the band gap tunability can be observed in these nanoparticles. Here, in this work, we emphasize on the synthesis of CZTS nanoparticles best suited for the photocatalytic application. Synthesis of rod-shaped CZTS nanoparticles has been done via hot injection colloidal route technique by varying the input precursor ratio i.e. Zn:Sn ratio as 1.2:1 2:1 and 4:1. Zn:Sn ratio is (>1, for Zn-rich) varied keeping other conditions and precursor ratios (Cu/(Zn + Sn), S/Metal = 1) constant. Different nanorods obtained were characterized by X-Ray Diffraction (XRD), Photoluminescence (PL) spectra and UV–Vis absorption spectroscopy and Transmission Electron Microscopy (TEM) respectively. The quality of different CZTS samples obtained was analyzed by XPS depth profiling analysis. Zn incorporation in both cases was optimized with respect to tin (Sn), phosphorus (P) and copper (Cu) for photocatalysis application. It was found that addition of more Zn into CZTS samples in precursors during synthesis may lead to lower incorporation of zinc amount, which results in varied properties advantageous for different photoactive applications. On the basis of different characterizations, CZTS nanorods synthesized with precursor ratio Zn: Sn = 2:1 was found to exhibits excellent photocatalytic activity as compared to other CZTS nanoparticles with precursor ratio Zn:Sn = 1.2:1 and 4:1 respectively, toward degradation of Malachite Green dye under sunlight. Graphical abstract: Schematic presenting ternary diagram showing various CZTS nanoparticles with different Zn:Sn ratio and the degradation mechanism for MG using CZTS nanoparticles with band gap 1.27 eV. Image 1 Highlights: Colloidal route synthesis of rod-shaped CZTS nanoparticles for higher aspect ratio. Precursor ratio i.e. Zn: Sn ratio variation to obtain varying stochiometry and band gap. Higher Zn:Sn in precursor leads to lower Zn incorporation w. r.t other constituting metals. Decrease in band gap has been observed due to higher incorporation of metal component. Low band gap and higher metal incorporation results in higher photocatalytic activity.